Analisis Kemampuan Koneksi Matematis Siswa Ditinjau dari Kecemasan Matematika - Astuti, Liana Widya; Nindiasari, Hepsi; Rafianti, Isna (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to analyze the relationship between mathematical anxiety and the mathematical connection ability of students in grades XI and XII of SMAS Plus Permata Insani Islamic School. This study used a descriptive quantitative approach involving 30 students. The selection of subjects was carried out using the purpsive sampling technique, such as studying row and series material. The instruments used were a mathematical anxiety questionnaire and a mathematical connection test. The data was analyzed using descriptive statistics, which included mean values, standard deviation, frequency distribution, and cross-tabulation. The results showed that most students experienced math anxiety in the medium category, which was related to the ability to make mathematical connections that were also in the medium category. Some students with high anxiety still show high connection ability, while students with low anxiety sometimes show low connection ability. These findings suggest that math anxiety is not the only factor affecting students' mathematical connection abilities, with other factors such as motivation and environmental support also playing an important role. This research suggests that teachers create an emotionally comfortable learning atmosphere and encourage increased motivation and appropriate learning strategies.